Pengaruh Substitusi Tepung Ikan dengan Tepung Larva BSF dalam Ransum terhadap Konsumsi Protein Kasar, Lemak Kasar dan Serat Kasar pada Burung Puyuh - Muhammad Yusuf; Kaharuddin Kaharuddin (Jurnal Syntax Admiration, 2024)
The research was carried out experimentally at the Non-Ruminant Livestock Laboratory, Faculty of Animal Husbandry, Hasanuddin University from April to June 2019. This research aims to determine the effect of substituting fish meal with BSF larvae meal in the ration on the consumption of crude protein, crude fat and crude fiber in quail. 60 female quail were used in this study using cages measuring 90 x 60 x 30 cm. This research method used a completely randomized design (CRD) consisting of four treatments and five replications, divided randomly based on treatment as follows: P0 Ration without adding BSF larval meal, P1 = BSF larval meal 3.183% (6.67% crude fish meal protein) , P2=BSF larval meal 6.370% (3.34% fish meal crude protein), P3=BSF larval meal 9.565% (0% fish meal crude protein). The variables observed were the consumption of crude protein, crude fat and crude fiber in quail. The data obtained were then analyzed using IBM SPSS Statistics 25 software. The results of the analysis of the effect of substituting fish meal with BSF larvae meal in the ration had no significant effect (P>0.05) on the consumption of crude protein, crude fat and crude fiber in quail.